Long-Term Hypercaloric Diet Consumption Exacerbates Age-Induced Dysmetabolism and Carotid Body Dysfunction - Melo, Bernardete F (2022)
Funding: This study was supported by the Portuguese Foundation for Science with a research grant EXPL/MED-NEU/0733/2021 and a contract for JS (CEEC IND/02428/2018).